The Church of Nazarene in Khayelitsha: Developing a missional spatial consciousness with special reference to COVID-19 - Mlambo, Ntandoyenkosi N. N. (HTS teologiese studies, 2024)
The legacy of apartheid spatial planning can still be seen in the dynamics of spaces in South Africa today. The elite (according to research is racialised and mostly white people) lives in well-located city areas, close to economic activity and rule social life that defines cities as stated in 2016 by the Socio Economic Rights Institute of South Africa (SERI). Alternatively, mostly black South Africans are confined to urban margins in densified and poorly serviced areas, with low rates of home ownership. The effects of these policies extend beyond the urban nature, as spaces on the margin by design tend to have fewer opportunities for education compared to urban areas, and there are spatial limits to black business ownership. This article seeks to discuss a case study on a church’s use of space during coronavirus disease 2019 (COVID-19), to show an inclusionary spatial dynamic that may be used in South African spaces. Firstly, it presents an overview of the unequal spatial dynamics in South Africa, particularly Cape Town, and dynamics during COVID-19. Secondly, it provides a historical overview of the Church of the Nazarene and its foundational beliefs. Moreover, it discusses a case study of renewed spatial dynamic in church using the Church of the Nazarene in Khayelitsha. Furthermore, the case study will be used to show the innovative way they reached their community during this time. The final part will discuss how this inclusive spatial dynamic reveals an innovative dynamic in the concept of the missional church, one that goes beyond the going out contextually, but allowing the outside in as well.Contribution: This article discusses the new spatial dynamic of the missional church which inspires inclusivity. The article uses literature around space, COVID-19, mission studies and church history. Furthermore, a semi-structured interview with a church leader at the Church of the Nazarene in Khayelitsha is used for a contextual case study.